Dose-Related Effectiveness of Andexanet Alfa for Reversal of Apixaban Anticoagulation in a Porcine Polytrauma Model - Rayatdoost, Farahnaz; Braunschweig, Till; Schöchl, Herbert; Rossaint, Rolf; Grottke, Oliver (Thrombosis and Haemostasis, 2023)
Background Andexanet alfa (andexanet) is a reversal agent for use in patients with life-threatening or uncontrolled bleeding treated with oral factor Xa (FXa) inhibitors. There are limited data on the dose–response relationship of andexanet and FXa inhibitor-related bleeding.Objective The aim of this study was to assess the dose-related effectiveness of andexanet in reducing blood loss, improving survival, and reversing apixaban anticoagulation in a porcine polytrauma model.Methods Apixaban was given orally to 40 male pigs for 3 days at a dose of 20 mg/d. On day 3, following bilateral femur fractures and blunt liver injury, animals (n = 8/group) received andexanet (250-mg bolus, 250-mg bolus + 300-mg 2-hour infusion, 500-mg bolus, or 500-mg bolus + 600-mg 2-hour infusion) or vehicle (control). Total blood loss was the primary endpoint. Coagulation parameters were assessed for 300 minutes or until death. Data were analyzed with a mixed-model analysis of variance.Results Administration of 250-mg bolus + 300-mg infusion, andexanet 500-mg bolus, and 500-mg bolus + 600-mg infusion significantly decreased total blood loss by 37, 58, and 61%, respectively (all p < 0.0001), with 100% survival. Andexanet 250-mg bolus was ineffective in reducing total blood loss (6%) and mortality (63% survival) versus controls. Andexanet 500-mg bolus ± infusion neutralized anti-FXa activity to less than 50 ng/mL. Andexanet neutralization of thrombin generation and thromboelastometry parameters was dose and infusion time dependent.Conclusion In a porcine polytrauma model with major bleeding on apixaban, andexanet dose dependently decreased anti-FXa activity. Lower anti-FXa levels (<50 ng/mL) with andexanet 500-mg bolus ± infusion were correlated with 60% less blood loss and 100% survival versus controls.
Keywords: anticoagulants; andexanet alfa; antidote; apixaban; polytrauma